آداب كتابة الحالة والتعليق عليها في الفيس بوك : دراسة تحليلية من خلال الصحيحين - Nor Faezah binti Hassan (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2014)
This research focuses on etiquettes of writing “posts” and “comments” in the Facebook based on the Sahihyn. The study defines Facebook and its relating terms to the subject matter. Moreover, this study explains how to create an account on the Facebook and the history and development of Facebook until today. This study also explains the recent updates of Facebook and how it attracts users. In the last chapter, the study shows various types of “post” and “comment” and also explains the common mistakes made by Facebook users when writing “posts” and “comments”. The main focus of the study is to explain the proper etiquettes in writing “post” and “comments” according to sahihyn hadith, specifically Sahih Bukhari and Sahih Muslim. The researcher used inductive, analytical and critical methods by studying and analysing the hadith from the sahihyn. The researcher found the sahihyn contains important general guidelines and particular etiquettes in writing “posts” and “comments” in Facebook.